Biotic- and abiotic-driven variations of the night-time sap flux of three co-occurring tree species in a low subtropical secondary broadleaf forest. Issue 3 (20th April 2018) - Wang, Qian; Gao, Jianguo; Zhao, Ping; Zhu, Liwei; Ouyang, Lei; Ni, Guangyan; Zhao, Xiuhua
Abstract: Although several studies on the night-time water use of different plant species have been reported, comparative studies under the same climatic conditions of a region are scarce. This study aimed to analyse the inter- and intraspecific variations in night-time water use in relation to environmental factors and to tree morphological features to understand and elucidate the possible underlying mechanisms. The sap flow of three co-occurring tree species in a low subtropical secondary broadleaf forest in South China was monitored using Granier-style sap flux sensors. All examined environmental factors except wind speed exerted significant influence on the daytime sap flows of Schima superba, Castanopsis hystrix and Michelia macclurei, but the impacts of all factors, including wind speed, on the night-time sap flux were trivial. These results indicated that sap flow was mainly used for water recharge at night. The morphological features of the trees, except tree height, significantly affected the daytime water use, but no morphological features significantly affected the night-time water use. We found that night-time water recharge was strongly affected by the maximum flux density. A principal component analysis showed that there were more intraspecific than interspecific variations in water transport. The results also revealed that the night-time water use and the percentage of night/day ( Q n / Q d ) of photosynthetic stem species ( C. hystrix and M. macclurei ) were greater than those of non-photosynthetic stem species ( S. superba ). Abstract : Aiming to analyse the inter- and intraspecific variations in night-time water use, we used Granier-style sap flux sensors to monitor the sap flow of three co-occurring tree species in a low subtropical secondary broadleaf forest in South China. A principal component analysis showed that there were more intraspecific than interspecific variations in water transport. The results indicated that sap flow was mainly used for water recharge at night, and the night-time water use and the percentage of night/day ( Q n / Q d ) of photosynthetic stem species ( Castanopsis hystrix and Michelia macclurei ) were greater than those of non-photosynthetic stem species ( Schima superba ).